Comparison of communication skill of medical students between activist and non activist - Mahdea Kasyiva; Warenda Wisnu Aulia Rakhman; Syaefudin Ali Akhmad (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2015)
Background: In Globalization era, the advancement in communication affects human included medical profession. It is crucial for a doctor to practice good communication in order to interact with patients and non-patients. Communication skill can be gained either in class or outside class by joining organization.Objective: The aim of this research is to compare communication skill between activist students (ASs) and non-activist students (NASs) in Medical Faculty of UII.Methods: This study methods was using a simulation of practical communication between a doctor and patients through observation method. This research uses non-specific patients and secondary data as result of Objective Structured Clinical Examination (OSCE), communication skill between activist students and non-activist students. The subjects are all ASs and all NASs.Result: There are summary of the difference between communication ability used by ASs and NASs. The number of ASs is equal with NASs. The highlights are ability in sense of connectivity, coherent information, sequence of questioning, non-verbal language such as eye-contact, and gestures.Conclusion: Involvement of student in organization does not significantly support the success in medical skill examination, in this case for Medicine Faculty students in UII batch 2013.